Content Analysis of Media Coverage of Childhood Obesity Topics in UAE Newspapers and Popular Social Media Platforms, 2014-2017 - Niyi Awofeso; Sara Al Imam; Arwa Ahmed (Kerman University of Medical Sciences, 2019)
The 2017 prevalence of obesity among children (age 5-17 years) in the United Arab Emirates (UAE) is 13.68%. Childhood obesity is one of the 10 top health priorities in the UAE. This study examines the quality, frequency, sources, scope and framing of childhood obesity in popular social media and three leading UAE newspapers from 2014 to 2017. During the review period, 152 newspaper articles from three leading national newspapers - Gulf News, The National and Al Ittihad - met the eligibility criteria for this study. There were 57 Facebook posts, 50 Twitter posts, 14 posted YouTube videos, and 13 Media releases on related to childhood obesity between 2014 and 2017. Childhood obesity was consistently problematized, primarily in health terms, but was not strongly linked to socio-economic and geographical factors. Childhood obesity was framed as being predominantly influenced by individual and parental behaviours more frequently (n = 76) compared with structural or environmental factors such as the roles of the food and beverage industry (n = 22). Unlike findings from studies with adult obesity, articles advocating individual behavior changes to address childhood obesity were relatively few (n = 29). Social media may be an effective way to help children overcome obesity, in part through online interaction with health care providers and health conscious obese peers. Areas for improvement in social media use to reduce childhood obesity prevalence in UAE include enhancing public engagement with social media posts on childhood obesity, as reflected in the numbers of Likes and Retweets or Shares.